Synthesis and characterization of Fe-Doped Zinc Oxide Rods - Abd Aziz_, Siti Nor Qurratu Aini (2014)
Chemical Vapor Deposition (CVD) technique is the most common vapor route technique uses by researchers to synthesize ZnO nanostructures. However, the current in-situ doping approaches using CVD do not give many flexibilities for the researchers to produce doped ZnO nanostructures. As the dopant solution is kept outside the furnace, the Aerosol Assisted - Chemical Vapor Depostion (AA-CVD) is a potential in-situ doping technique because it offers many advantages such as flexibility of controlling the doping concentration, doping duration, type of dopant precursor and possibility of mass production of doped nanostructures. This project started by setting up a CVD system to synthesize undoped ZnO rods without using foreign catalyst. The study indicated that the optimum synthesis condition for synthesizing undoped ZnO rods was using 0.3 g Zn powder, 30 min synthesis duration, and 5 cm distance of Si substrates from Zn powder at 650 °C. The average length, diameter, aspect ratio and areal density of undoped ZnO rods are 2.99 ± 0.13 μm, 0.54 ± 0.05 μm, and 5.6 ± 0.3, 2.9 ± 0.9 rods/m2, respectively. Subsequently, ex-situ Fe-doping was performed via spray pyrolysis on the pre-grown ZnO rods. The physical properties of Fe-doped ZnO rods prepared by ex-situ doping would be used to compare with the Fe-doped ZnO rods prepared by in-situ doping in the subsequent phase. The presence of Fe 2p1/2 and Fe 2p3/2 peaks which were located at 722.3 eV and 705.7 eV, respectively in (X-Ray Spectroscopy) XPS analysis reveals the substitution of Fe2+ with Zn2+ in the ZnO rods. As compared to undoped ZnO rods, the Fe-doped ZnO rods exhibited poor photocatalytic activity in degradation of xxiii RhB dye under UV irradiation. Lastly, in-situ Fe-doping was successfully performed to synthesize Fe-doped ZnO rods using AA-CVD. At the synthesis condition of 0.05 M dopant solution, doping duration of 60 min and 650 °C, Fe-doped ZnO rods were synthesized. The average length and diameter were 4.45 ± 0.26 μm and 0.71 ± 0.05 μm, respectively. The Fe 2p1/2 and Fe 2p3/2 peaks of XPS which located at 718.4 eV and 704.8 eV, respectively present in the form of Fe3+ state. As compared to ex-situ doping, the Fe-doped ZnO rods synthesized by in-situ doping demonstrated similar properties, i.e., (i) the shift of (002) X-Ray Diffraction (XRD) peak to a smaller 2θ; (ii) the reduction of Iuv/Ivis ratio of room temperature Photoluminescence (PL) measurement and; (iii) poor photodegradation activity. Although Fe2+, and Fe3+ state were obtained for both ex-situ and in-situ doping respectively, both techniques similarly showed poor photodegradation activity. The Fe-doped ZnO rods with poor photocatalytic activity but good UV absorption capability could be a potential UV shielding candidate.